Domestic abuse victims' perceptions of abuse and support: a narrative study. Issue 1 (9th March 2015) - Spruin, Elizabeth; Alleyne, Emma; Papadaki, Ioanna
Abstract : Purpose: – While there is a large body of research exploring the various avenues of support for domestic abuse victims and the risk factors which put women at risk of victimization, there is little research exploring the perceptions of these women. The purpose of this paper is therefore to explore the personal views of victimized women; in particular, the risk factors that they believe put them at risk for abuse and what they feel support services should offer. Design/methodology/approach: – In total, 12 women were interviewed about their experiences of domestic violence. Interviews were analyzed using thematic analysis which resulted in three themes: first intimate relationship; quality of life; and supporting services. Findings: – The results from the analysis highlighted some prominent risk factors and, most importantly, emphasized the need for alternative forms of support. Overall, the findings provide an innovative way of viewing domestic violence by understanding it through victim's narratives, which can further aid to inform current support services within the UK and elsewhere. Research limitations/implications: – The quality of life around the time of abuse is a factor that should be explored further in relation to the victimization of women. Practical implications: – Ambivalent first sexual encounters may be an important risk factor for future relationship violence. Social implications: – Support services for domestically abused women need to offer more internal support for vocational and educational services. Originality/value: – There is little research exploring the personal views and perceptions of victimized women, in particular, the risk factors that they believe put them at risk for domestic abuse and what they feel support services should offer. The value of this research is therefore founded in the exploring this gap in literature and provide victims with a voice to aid researchers in understanding domestic abuse from another perspective. Investigating a victim's personal account is one pathway into beginning to understand the underlying thought processes and beliefs they attach to an event. If themes within a personal narrative account could be identified within victims of domestic abuse, it may allow a new aetiological perspective to develop in regard to the understanding and needs of abused women.